Implementasi Agama Dalam Mewujudkan Keluarga Sakinah - Farah Chalida Hanoum T. (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
Religion plays an important role in a family life. As a Muslim family, we should continuously apply Islamic values as a foundation in pursuing the family life. This foundation functions as a guidance and direction for them to solve the problems of life so that peaceful (sakinah) family can be achieved. When religious values are well implemented in the family life, the following conditions will be attained: every family member will have a sense of affection, be closed to, have no prejudice, trust, regard, and advise one another, as well as apply problem oriented perspective in playing their roles and functions in the family.